A Study on the Transversal Optical Mode in Amorphous Gallium Arsenide - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
Contributions to the far-infrared spectrum corresponding to both dynamical and structural disorders in a-GaAs are examined when frequency coincides with the transversal optical mode. Under these circumstances, dipole moment matrix element is discussed.